2020
DOI: 10.2174/1874609812666190917155400
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and Dementia: A Long and Complicated Relationship

Abstract: Background: There is a huge demand for efficient strategies for maintaining cognitive wellbeing with age, especially in the context of population aging. Dementia constitutes the main reason for disability and dependency in the elderly. Identification of potential risk and protective factors, as well as determinants of conversion from MCI to dementia, is therefore crucial. In case of Alzheimer’s disease, the most prevalent dementia syndrome amongst the members of modern societies, neurodegenerative processes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 114 publications
0
36
0
Order By: Relevance
“…However, due to their pleiotropic effect, we should not limit their use. Experimental studies have shown that statins reduce Ab production, inhibit inflammatory reactions, protect neurons from neurotoxicity induced by pathological protein, and oxidative stress [8,16]. We divide statins according to their properties.…”
Section: Statins Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…However, due to their pleiotropic effect, we should not limit their use. Experimental studies have shown that statins reduce Ab production, inhibit inflammatory reactions, protect neurons from neurotoxicity induced by pathological protein, and oxidative stress [8,16]. We divide statins according to their properties.…”
Section: Statins Treatmentmentioning
confidence: 99%
“…In the autopsy of brains affected by dementia, 24-OH reduction and 27-OH increase can be seen. Zuliani et al suggest that 24 (S)-hydroxychowww.journals.viamedica.pl/medical_research_journal lesterol levels may be elevated in the early stages of AD due to systemic inflammation [8]. It is suggested that 24S-hydroxycholesterol (SHC) is a biochemical marker of neurodegenerative diseases, as it is responsible for the transport of cholesterol through its enzymatic oxidation [1,27].…”
Section: The Metabolism Of Brain Cholesterolmentioning
confidence: 99%
See 3 more Smart Citations